Addressing the Category of “Freedom” from a Religious and Philosophical Perspective. Defining the Scope of “Freedom” in Selected Works by Lyudmila Ulitskaya - Kuca, Zoja; Kucy, Aleksy (W kręgu zagadnień języka, literatury i kultury: Księga jubileuszowa dedykowana Profesorowi Jarosławowi Wierzbińskiemu, 2022)
The article is an attempt to analyse the category of freedom in the Russian religious and philosophical thought as well as interpreting this category in Lyudmila Ulitskaya’s selected works. The article offers some reflections on freedom in the view of Aleksey Khomyakov, Ivan Ilyin, Nikolai Berdyaev, Fyodor Dostoevsky, and other Russian intellectuals who considered is a substitutional element of human life and human functioning. The category of freedom presented in Lyudnila Ulitskaya’s works, Daniel Stein, Interpreter, and The Kukotsky Enigma, About Body and Soul, uncovers different facets of this phenomenon. The Russian writer approaches the multiplicity of interpretations of freedom through extraordinary figures, on the one hand, and through difficult subjects, on the other: human relations with God, survival of WW2, methods employed by the Soviet regime in their struggle with the Jews, the Holocaust. These are age-old themes in which the limits of freedom of an individual and the responsibility for the fate of others come to the fore.